Chile : Institutions and Policies Underpinning Stability and Growth - Kalter, Eliot (Occasional Papers; Occasional Paper ;, 2004)
This paper presents the primary institutions and economic policies that have led to Chile's remarkable record of stability and growth over the past twenty years. The core of this policy stance is the combination of fiscal discipline and an open trade policy regime, together with carefully sequenced financial liberalization with in a strengthened regulatory framework.Chile has succeeded in sustaining these policies-despite external and domestic forces to the contrary-because of carefully designed institutional arrangements that encourage policies oriented toward long-term success.